Cardiovascular disease in chronic kidney disease: a clinical update from Kidney Disease: Improving Global Outcomes (KDIGO) - Herzog, Charles A.; Asinger, Richard W.; Berger, Alan K.; Charytan, David M.; Díez, Javier; Hart, Robert G.; Eckardt, Kai-Uwe; Kasiske, Bertram L.; McCullough, Peter A.; Passman, Rod S.; DeLoach, Stephanie S.; Pun, Patrick H.; et al. (Kidney international, 2011)
Cardiovascular morbidity and mortality in patients with chronic kidney disease (CKD) is high, and the presence of CKD worsens outcomes of cardiovascular disease (CVD). CKD is associated with specific risk factors. Emerging evidence indicates that the pathology and manifestation of CVD differ in the presence of CKD. During a clinical update conference convened by the Kidney Disease: Improving Global Outcomes (KDIGO), an international group of experts defined the current state of knowledge and the implications for patient care in important topic areas, including coronary artery disease and myocardial infarction, congestive heart failure, cerebrovascular disease, atrial fibrillation, peripheral arterial disease, and sudden cardiac death. Although optimal strategies for prevention, diagnosis, and management of these complications likely should be modified in the presence of CKD, the evidence base for decision making is limited. Trials targeting CVD in patients with CKD have a large potential to improve outcomes.
Gesehen am 22.09.2022